Smart Sensors and Intelligent Analysis: A Literature Review on More Effective Early Warning Systems with IoT and Machine Learning - Mustamin, Syaiful Bachri; Atnang , Muhammad; Sahriani , Sahriani; Fajar, Nurhikmah; Sari, Sri Kurnian; Pahlawan , Muammar Reza; Amrullah, Mujahidin (Science Tech Group, 2024)
The IoT system described in the article